1963
DOI: 10.1084/jem.118.4.527
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Antigens of Group a Streptococci

Abstract: The immunoelectrophoretic characteristics of the known cellular antigens of serotype 17, Group A streptococci have been presented. These include C, M, T, and polyglycerophosphate. In addition, three hitherto undescribed antigens of serotype 17 have been encountered. The F antigen occurs in most serotype 17 strains, has a faster electrophoretic mobility than M, appears in acid, distilled water, and other extracts of harvested cells, is released from the cells in large quantity into the culture me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…wall proteins, such as T and R, have been described (4,11). The present investigation showed that patterns obtained by acrylamide gel electrophoresis of streptococcal cell walls were characteristic for selected M types of group A streptococci.…”
supporting
confidence: 59%
“…wall proteins, such as T and R, have been described (4,11). The present investigation showed that patterns obtained by acrylamide gel electrophoresis of streptococcal cell walls were characteristic for selected M types of group A streptococci.…”
supporting
confidence: 59%
“…The occurrence of antibodies to streptococcal Group A carbohydrate in man has been described by several authors (4)(5)(6)(7)(8). Halpern human sera (6).…”
Section: Discussionmentioning
confidence: 99%
“…Since Ig receptors are essential for antigen recognition [3], it has been suggested that their loss, as a result of antigendriven maturation, could cause a reduction in the capacity of lymphocytes t o make contact with and be stimulated by anti- Attempts have previously been made t o define intracellular molecular changes which probably occur concurrently with the loss of immunoglobulin receptors, after the first antigen contact. Autoradiographic studies during immunocyte maturation have demonstrated a shift from blast cells, intensively synthesizing RNA, to plasma cells, actively synthesizing protein, without concommitant RNA synthesis [8,9]. This shift was further analyzed by examining the Actinomycin D sensitivity of antibody-producing cells in chicken spleen fragment cultures at various times after in v i v o immunization [ 101.…”
Section: Introductionmentioning
confidence: 99%